Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada PT Central Proteina Prima Tbk. - Julian Danu; Supriyanto; Dody Kurniawan (Draf Solusi Indonesia, 2025)
This study analyzes the effect of work motivation and work environment on employee performance at PT Central Proteina Prima Tbk. The population consists of 81 Consumer Goods employees at the Head Office, using a saturated sampling method. Data were collected via a questionnaire distributed through Google Forms and analyzed using SPSS version 30. The results show that work motivation and work environment positively and significantly influence employee performance, both individually and simultaneously. Their combination plays a crucial role in enhancing employee performance.